Bíblia: palavra de Deus em linguagem humana: sua interpretação no passado e na contemporaneidade - Iacono, Christian Santiago Lo (2014)
The history of biblical interpretation is witness to the fact that whether to use the more human approach or the more supernatural approach to the Bible has always been cause for dissention in the Christian community. This interpretative diversity is due, in great part, to the understanding which one has about the nature of the Bible: sometimes it is divinized, other times it is treated as a merely human book. Adopting a biblical-systematic theological focus, the research verified that the Bible, considered the Word of God in human language, needs to be interpreted respecting this tension, since it gathers together human witnesses of revealing experiences of God. This in no way affects its character as Word of God, since the inerrancy of the Bible is in its message, the apex of which is the revelation of Jesus Christ. In the era of Post-modernity, in which the author, text and reader are de-constructed, the existence of meaning in the text presents itself as a theological issue. Although the intention of the author may not be knowledge which one can objectively obtain, there exist elements in the text which orient the reader to see it as a definite communicative action. The literal meaning, or the literary meaning, is the one which respects the author s intention, which can be discovered through the historical-critical method. On the other hand the sensus plenior results from the geographical and temporal distances between the text and the reader, who discovers in it new potentialities. The last stage of understanding is the personal appropriation of the biblical text, which is taking in the intended communicative action through the help of the Holy Spirit, which, then, imparts upon the text new meaning in the face of new times. Word and Holy Spirit together form the act of God s speaking. To understand the Bible one, fundamentally, needs to begin walking in its path.